Do nonfinancial firms hold risky financial assets? Evidence from Germany - Daniel Hoang; Fabian Silbereis; Raphael Stengel (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2021)
Recent empirical evidence suggests that US industrial firms invest heavily in noncash, risky financial assets. Using hand-collected data on financial portfolios of German firms, we show that risky asset holdings are not an anomaly unique to the US. We find that industrial firms in Germany invest 11.6% of their financial assets in noncash and risky assets. Value-weighted, this percentage increases to 25.4%. While the equally-weighted average is substantial, it is clearly lower (5 percentage points or 30% in relative terms) than that in the US. After accounting for cross-country compositional differences (especially the dominance of large firms in the US technology sector), this difference in risky financial asset holdings decreases but remains at 3 percentage points. The remaining difference is driven by institutional differences that affect the relationship between firm characteristics and risky financial asset holdings in the two countries. In contrast to the US, German firms largely follow the precautionary savings motive and do not seem to misappropriate their funds when shifting them towards riskier asset allocations. Our results have implications for how asset management by nonfinancial firms should be regulated.
Keywords: G31; G32; G34; G38; G11; 330; Cash Policy; Financial Portfolio; Precautionary Savings; Liquidity Management